Pengaruh Disiplin dan Kualitas Pelayanan terhadap Tingkat Kepuasan Pengguna Layanan Publik (Studi Kasus pada Pengadilan Negeri Metro) - Setiarso, Setiarso; Habiburahman, Habiburahman (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to analyze the influence of work discipline and service quality on the level of satisfaction of public service users. The focus of the study is directed at determining the extent to which work discipline of civil servants and the quality of service provided can increase public satisfaction as service users. The research method used is a quantitative approach with data collection techniques through the distribution of questionnaires to service user respondents. The data obtained were analyzed using multiple linear regression analysis, supported by validity and reliability tests, and classical assumption tests to ensure the feasibility of the research model. The results of the study indicate that work discipline has a positive and significant effect on public service user satisfaction. In addition, service quality also has a positive and significant effect on public service user satisfaction. Simultaneously, work discipline and service quality have a significant influence on the level of satisfaction of public service users, which means that the better the work discipline of civil servants and the quality of service provided, the higher the level of public satisfaction. The conclusion of this study is that increasing public service user satisfaction is strongly influenced by work discipline of civil servants and service quality. Therefore, it is recommended that relevant agencies increase the consistency of the application of work discipline through continuous monitoring and evaluation, and continue to improve service quality in the aspects of reliability, responsiveness, assurance, empathy, and physical evidence to realize professional public services that are oriented towards public satisfaction.